Two-dimensional hexagonal V2O nanosheet and nanoribbons. (23rd February 2015) - Tang, Zhen-Kun; Geng, Wei; Zhang, Yan-Ning; Zhang, Deng-Yu; Liu, Li-Min
Abstract: A novel two-dimensional hexagonal V2 O was proposed and investigated through first-principles calculations. The hexagonal V2 O nanosheet exhibited a V–O–V sandwich structure. The stability of monolayer V2 O was verified by formation energy and phonon frequency calculations. The calculations of electronic properties using a hybrid density functional method indicate that monolayer V2 O is a nonmagnetic metal. However, the zigzag nanoribbon exhibited robust edge magnetism, while the armchair nanoribbon was found to be a nonmagnetic semiconductor with a direct band gap. The variety of electronic properties of monolayer V2 O nanosheets and nanoribbons opens up tremendous opportunities for nano-electronic and spintronic devices.